Exploring and Evaluating "TaPrEC+mBot" Environment with Preschool Children - Carbajal, Marleny Luque; Baranauskas, M. Cecília (Anais do Workshop de Informática na Escola (WIE); 2019: Anais do XXV Workshop de Informática na EscolaDO - 10.5753/cbie.wie.2019.521, 2019)
Contact with programming has a positive impact on the development of cognitive and socio-emotional skills in children. However, programming can be a challenging activity for young children. There are many studies that suggest that tangible environments can engage children to explore basic programming concepts more easily. In this paper, we present results obtained during a Case Study conducted to introduce preschool children into programming through TaPrEC+mBot, an environment that allows to program a robot car by arranging wooden programming blocks. The results suggest that our environment is attractive and interesting for young children, although it still needs to adjust labeling programming blocks in order to facilitate their learning in early childhood settings.